2020
DOI: 10.1371/journal.pone.0228385
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II triggers RIPK3-MLKL-mediated necroptosis by activating the Fas/FasL signaling pathway in renal tubular cells

Abstract: Our earlier studies proved that RIPK3-mediated necroptosis might be an important mode of renal tubular cell death in rats with chronic renal injury and the necroptotic cell death

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…KIRC patients in high-risk group exhibited the upregulated expressions of FASLG and ZBP1 but a downregulated TLR3 expression. The pathway of Fas and Fas Ligand (FasL, FASL, FASLG) can initiate necroptosis upstream of RIPK3 and MLKL in renal tubular epithelial cells [34]. The cell surface FasL induces Fas-mediated killing, while autocrine secretion of soluble FasL can protect RCC cells from cytotoxic lymphocytes killing [35].…”
Section: Discussionmentioning
confidence: 99%
“…KIRC patients in high-risk group exhibited the upregulated expressions of FASLG and ZBP1 but a downregulated TLR3 expression. The pathway of Fas and Fas Ligand (FasL, FASL, FASLG) can initiate necroptosis upstream of RIPK3 and MLKL in renal tubular epithelial cells [34]. The cell surface FasL induces Fas-mediated killing, while autocrine secretion of soluble FasL can protect RCC cells from cytotoxic lymphocytes killing [35].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, RIPK1 and RIPK3 independently influence inflammation without affecting cell death ( 59 ). Earlier studies have shown that RIPK3-related necroptosis is the primary form of renal tubular epithelial cell death in rats with chronic renal injury ( 60 ). The hyperglycemia/AGEs-activated intrarenal RAAS system can increase the levels of renin and angiotensin in renal cells ( 61 , 62 ).…”
Section: Necroptosismentioning
confidence: 99%
“… 2 79 Fas/FasL is well-known to induce RIPK-MLKL-mediated necroptosis as well as caspase-dependent apoptosis. 80 81 82 Milhas et al 83 have shown that D609 treatment enhances ceramide increase, leading caspase-independent cell death in response to FasL under zVAD-fmk-mediated inhibition of caspases in Jurkat cells. However, as the authors did not demonstrate the involvement of RIPK and MLKL activation, it was unclear whether this was necroptosis or not.…”
Section: Signal Transduction Is Regulated By Sms-mediated Ceramide/smmentioning
confidence: 99%